S123 The Role of Nasal Potential Difference Testing in Difficult Cases of Possible Cystic Fibrosis. (19th November 2012) - Simmonds, N; Pabary, R; Ya-Tung, I; Bilton, D; Alton, EWFW; Davies, JC
Abstract : The European CF Diagnostic Working Group guidelines include nasal potential difference (nPD) testing when conventional tests (sweat chloride/ CFTR mutation analysis) are inconclusive. This specialist measure of epithelial ion transport is available in relatively few centres throughout the UK and Europe and therefore may not be readily considered as a diagnostic option. We have been offering a clinical service for several years, for both our own patients and those referred in. Here, we report the results of a retrospective audit over a 2.5 year period with an aim to increase awareness and understanding of the test. Between March 2009 and Sept 2011, 66 patients (58% female) underwent testing. Median (range) age was 18 (2–67) years. Children under the age of 8 were most commonly tested whilst under anaesthetic for a bronchoscopy. 59% of patients were referred from other centres. The majority of sweat chloride results (52%) were in the 30–60 mEq borderline range. 95% had undergone first-line CFTR mutation analysis: 62% had none, 37% had one and 1 subject had 2 mutations, one of which was considered a 'sequence variant'. One child was unable to tolerate the procedure; 6% of traces were uninterpretable due to presumed nasal inflammation. Overall, the nPD results in the context of other features led to a diagnosis of variant/atypical CF in 18%; abnormality in chloride secretion was more sensitive than sodium absorption. We were able to rule out CF 'to the best of current diagnostic ability' in 60% including 6 of 8 patients diagnosed with CF in early childhood, but now considered so unlikely to have the disease that re-investigation was warranted. In a further 13% of cases, nPD was of good quality but was difficult to categorise; in addition to the full CFTR gene sequencing performed routinely, we will investigate these patients for mutations in genes such as ENaC. Nasal PD was well tolerated and helpful in clarifying the diagnosis in the majority (78%) of patients referred. It should be considered in patients for whom, despite careful work up, a diagnosis of CF is difficult to confirm or rule out.